2015
DOI: 10.1186/s12878-015-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Decreased erythrocyte nucleoside transport and hENT1 transporter expression in glucose 6-phosphate dehydrogenase deficiency

Abstract: BackgroundGlucose-6-phosphate dehydrogenase (G6PD) deficiency is associated with erythrocyte sensitivity to oxidative damage and hemolytic crises. In β-thalassemia major, where hemoglobin instability imposes oxidative stress, erythrocytes show reduced hENT1 nucleoside transporter expression and decreased nucleoside uptake. This study investigated hENT1 expression and nucleoside transport in G6PD-deficient erythrocytes to determine if decreased hENT1 activity might be a contributory feature in the variable path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Given the consequences of adenosine A2B‐receptor signalling on HbS polymerisation and RBC sickling, 5 a possible role for erythrocyte ENT1 transporter regulation in SCD pathophysiology remains to be investigated. A limitation of our present study is that measurements of erythrocyte ENT1 were based on immunoblots and flow cytometry, not on nucleoside uptake, although several studies have reported a good concordance of ENT1 expression and nucleoside transport 14–16 …”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Given the consequences of adenosine A2B‐receptor signalling on HbS polymerisation and RBC sickling, 5 a possible role for erythrocyte ENT1 transporter regulation in SCD pathophysiology remains to be investigated. A limitation of our present study is that measurements of erythrocyte ENT1 were based on immunoblots and flow cytometry, not on nucleoside uptake, although several studies have reported a good concordance of ENT1 expression and nucleoside transport 14–16 …”
Section: Discussionmentioning
confidence: 89%
“…A limitation of our present study is that measurements of erythrocyte ENT1 were based on immunoblots and flow cytometry, not on nucleoside uptake, although several studies have reported a good concordance of ENT1 expression and nucleoside transport. [14][15][16] The moderate but significant correlation of ENT1 expression levels in CD71 + reticulocytes and CD71 − mature RBC indicates that the variable erythrocyte ENT1 expression in patients with SCD is likely to be determined at least in part by its expression level in precursor cells. 6 In the mouse, erythroid expression of the Slc29a1 gene has been shown to be part of a complex regulatory network linked to adenosine homeostasis that involves its opposite regulation by the GATA-binding protein 2 (GATA2) and GATA1 transcription factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular adenosine signaling serves regulatory functions in inflammation, in acute lung injury ( 48 ) and in the O 2 delivery ability of red cell targets through boosting the production of 2,3-BPG ( 46 ). Nucleoside transporters assist in the control of plasma adenosine levels, and notably, decreased nucleoside transporter hENT1 [that also mediates hypoxanthine transport ( 49 )] expression and activity was detected in G6PD − RBCs ( 50 ). In G6PD − FFP, adenosine was correlated with red-cell vesiculation, lipid peroxidation, hemolysis, DAG, oxidized glutathione, and uric acid/allantoate levels, suggesting more influential effects compared with the control FFP and a second level of intercellular signaling potential.…”
Section: Discussionmentioning
confidence: 99%